Kecanduan Media Sosial dan Efeknya pada Perilaku Masyarakat Jabodetabek terhadap Iklan di Instagram - Satinputra, Akbarilman; Kencana, Nala Akhmad; Ekaputra, Lukas; Leonardo, Yosua (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2020)
This study aims to identify the effect of habitual and perceived ease of use on psychological dependence on Instagram and to explore the relationship between dependence and attitudes of Instagram users towards ads on Instagram. Four factors in the use of Instagram, among others; concepts, habits, perceived ease of use of Instagram, psychological dependence, which were analyzed were identified as influencing customer behavior towards advertisements on Instagram. Questionnaires with quantitative methods were adopted and adapted from previous studies. Questionnaires were given to people in Jabodetabek. A total of 309 collected questionnaires were analyzed using linear regression analysis for tested the effect of habitual and perceived ease of use on psychological dependence on Instagram and to explore the relationship between dependence and attitudes of Instagram users towards advertising on Instagram. There is a relationship between the perception of using Instagram, with user habits as the habit of using Instagram is related to the psychological dependence of users on the Instagram application. Perceptions of using Instagram are unrelated and insignificant to the psychological dependence of Instagram users. Psychological dependence and perceived use of Instagram led to a significant relationship and positive attitude towards advertising on Instagram.